Electrocatalytic Shilov chemistry for the oxidation of aliphatic groups - Liu, Sophie F.; Nusrat, Faria (Molecular catalysis, 2019)
[Display omitted] •A platinum(II) salt is an electrocatalyst for the hydroxylation of aliphatic groups.•Both methane and p-toluenesulfonic acid can be converted to their alcohols.•Judicious control of the applied potential is necessary to effect catalysis.•No additional co-catalyst is needed to observe electrocatalysis. An existing chemistry for the selective oxidation of methane to methanol is the homogeneous platinum(II)-based Shilov system, but limiting its practical implementation is its use of platinum(IV) as the terminal stoichiometric oxidant. However, an examination of the Shilov cycle suggests that electrochemical regeneration of the Pt(IV) oxidant would allow for the system to be catalytic in platinum. We demonstrate that through judicious selection of applied electrical bias to near the initial open circuit potential of the reaction mixture (∼560 mV vs Ag/AgCl), Shilov-type hydroxylation of p-toluenesulfonic acid as a surrogate for methane can be electrocatalytically effected over a homogeneous Pt(II) catalyst, Na2PtCl4 in 0.5 M H2SO4, giving 8% yield of the alcohol product at 4.5 mol% catalyst loading with good Faradaic efficiency and without a co-catalyst or additional redox mediator. Methane can also be converted to methanol electrocatalytically with this system.